Ultra-wideband radio technology potential and challenges ahead. - Porcino, D. (IEEE Communications magazine)
An unprecedented transformation in the design, deployment, and application of short-range wireless devices and services is in progress today. This trend is in line with the imminent transition from third- to fourth-generation radio systems, where heterogeneous environments are expected to prevail eventually. A key driver in this transition is the steep growth in both demand and deployment of WLANs/WPANs based on the wireless standards within the IEEE 802 suite. Today, these short-range devices and networks operate mainly standalone in indoor home and office environments or large enclosed public areas, while their integration into the wireless wide-area infrastructure is still nearly nonexistent and far from trivial. This status quo in the short-range wireless application space is about to be disrupted by novel devices and systems based on the emerging UWB radio technology with the potential to provide solutions for many of today's problems in the areas of spectrum management and radio system engineering. The approach employed by UWB radio devices is based on sharing already occupied spectrum resources by means of the overlay principle, rather than looking for still available but possibly unsuitable new bands. This novel radio technology has received legal adoption by the regulatory authorities in the United States, and efforts to achieve this status in Europe and Asia are underway. This article discusses both the application potential and technical challenges presented by UWB radio as an unconventional but promising new wireless technology.